Urea super granules with deep placement - Ambler, Kate; Bloem, Jeffrey R.; McNamara, Brian (International Food Policy Research Institute, 2025)
Urea deep placement, an alternative to traditional broadcast methods, consists of applying urea super granules (USG) directly into the soil next to the root of the plant and beyond the roots of weeds. Traditionally, farmers broadcast prilled urea fertilizer on top of their plots, which is associated with high rates of nitrogen loss, leading to reduced crop yields and environmental damage, especially among rice farmers. In contrast, the use of USG deep placement better contains nitrogen in the soil, facilitating its absorption into crops and improving nitrogen use efficiency. In this way, USG can reduce nitrogen losses along with the associated economic and environmental consequences.